The relationship between organizational culture, information technology, and the effectiveness of internal auditing: A study in Vietnam - Que, Nguyen Thi; Duyen, Nguyen Thi Hanh; Thuy, Tran Thi Thu; Bac, Dang Thi (Edelweiss Applied Science and Technology, 2025)
In the modern business context, organizational culture, information technology, and the effectiveness of internal auditing are closely interconnected and mutually influential. A transparent and innovation-driven corporate environment enhances the efficiency of internal auditing. At the same time, the application of information technology, such as process automation and data analytics, improves the accuracy and speed of audits. When organizational culture supports auditing and effectively leverages technology, internal auditing not only ensures compliance but also contributes to better risk management, fostering sustainable business growth. This study examines the relationship between organizational culture, information technology, and the effectiveness of internal auditing. The research team employs a quantitative approach using a Likert scale ranging from 1 to 5 and SPSS 22 software, based on data collected from 156 internal auditors in Vietnamese enterprises. The findings indicate that the use of information technology is crucial for enhancing the effectiveness of internal auditing. Furthermore, organizational culture plays a vital role as a mediator in the relationship between information technology and the effectiveness of internal auditing.